Interactive learning in islamic education using FROG VLE: readiness and proficiency of teachers / Mohd Faiz Mohd Baharan, Mohd Nor Mamat and Zawawi Temyati - Mohd Baharan, Mohd Faiz; Mamat, Mohd Nor; Temyati, Zawawi (2021)
The evolution in educational delivery from using chalk and black board to computer and multimedia has apparently resulted in a more attractive and incremental interest among students during their learning session. Recently, the Ministry of Education Malaysia has implemented proactive and dynamic initiative by introducing the Frog Virtual Learning Environment (FROG VLE) application. In general, FROG VLE is a virtual learning website that is provided to all students, teachers, and parents to get any required information and learning development in school education including the Islamic Education subject. This study aimed to identify the level of readiness and proficiency of Islamic Education teachers towards the utilization of Frog VLE in their teaching and learning activities. This study used a quantitative method where 2 sets of questionnaires of readiness and proficiency have been constructed with the reliability score at 0.93 and 0.96. Result shows that the level of readiness among teachers towards the use of Frog VLE is high with the mean of 3.76, but the level of skills in Frog VLE application among teachers is moderate with the mean of 3.17. These show that the Islamic Education teachers are aware and ready to venture into interactive learning using FROG VLE, but they still lack skills that need more effort and programmes in preparing them with higher skills focusing on Frog VLE in school